PENGARUH SK. MENDIKNAS NO. 36/O/D/2001 TERHADAP PERKEMBANGAN PERGURUAN TINGGI SWASTA DI LINGKUNGAN KOPERTIS WILAYAH VII - Subroto Subroto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The purposes of this research are to formulate/ to identify the apparent impact of the policy of credit point assessment of lecturer academic position as stated in national education minister’s decree No. 36/D/O/2001 and to give input to the decision maker to consider the impact when they make correction toward the policy. Besides that, its purpose is to provide the description to the leaders of private colleges and to the lecturers who are instructed to work there and the foundation lecturer that the academic position is very important both for themselves and for increasing the private college independence.The result of this research shows that there is increase quantitatively of full time lecturer qualification, the ratio between the number of full time lecturers and the number of student and graduates. However, the quantitative increase is not comparable with the expected target of a policy such as accreditation, lecturers ranks, examiners and so on.There are some factors which impede the achievement of private college independence of coordinator of private college of region VII that is policy factor itself, aparatus as the policy operators and the motivation of the private colleges.Related to the problem above, it is necessary to create monitoring mechanism which enables the private colleges to encourage to increase the qualification of the full time lecturers periodically both through the level increase of formal education (S-2/S-3) and through the increase of their rank of academic position, and the private colleges are given real authority in carrying out their functions.